MiR-204 is associated with an endocrine phenotype in human pancreatic islets but does not regulate the insulin mRNA through MAFA. Issue 1 (December 2017) - Marzinotto, Ilaria; Pellegrini, Silvia; Brigatti, Cristina; Nano, Rita; Melzi, Raffaella; Mercalli, Alessia; Liberati, Daniela; Sordi, Valeria; Ferrari, Maurizio; Falconi, Massimo; Doglioni, Claudio; Ravassard, Philippe; et al.
Abstract miR-204 has been proposed to modulate insulin expression in human pancreatic islets by regulating the expression of theMAFA transcript, and in turn insulin transcription. We investigatedmiR-204 expression in pancreatic endocrine tumors (PET), a panel of human tissues, tissues derived from pancreatic islet purification, and in induced pluripotent stem cells (iPSCs) differentiated towards a pancreatic endocrine phenotype by quantitative real time RT-PCR or droplet digital PCR (ddPCR). In addition, we evaluated the effect ofmiR-204 up- or down-regulation in purified human islets and in the EndoC-βH1 cell line, as an experimental model of human pancreatic β cells. Our results confirm thatmiR-204 was enriched in insulin producing PET, in β cells within healthy pancreatic islets, and highly expressed in EndoC-βH1 cells. Moreover, in iPSCsmiR-204 increased stepwise upon stimulated differentiation to insulin producing cells. However, up- or down-regulation ofmiR-204 in human islets and in EndoC-βH1 cells resulted in modest and not significant changes of theMAFA andINS mRNAs measured by ddPCR or c-peptide release. Our data confirm the association ofmiR-204 with a β cell endocrine phenotype in human pancreatic islets, but do not support its direct role in regulating the levels of insulin mRNA through MAFA.